Digital Human Assets and Psycho-digital Risks. Concept and recommendations - Tello de la Torre, Claudia; Perez, Vanesa; Martí-Noguera, Juan José (Revista Venezolana de Gerencia, 2021)
Nowadays, 60% of humanity is digitally connected, implying the generation of data and content. In this sense, the objective of this article is to discuss the relationship between the concepts of Human Digital Assets and Psycho-digital Risks. The former comprises digital information linked to a person, and the latter is conceived as the potential danger arising from the interaction of people and organizations due to interaction with networked technologies without sufficient knowledge. Through a qualitative methodological approach and a documental research design, both concepts are addressed, in order to provide their identification, evaluation, and integration in the management of human digitization processes. This paper does not intend to formulate a methodology for its quantification, but rather to motivate and raise awareness of the need to rethink digital literacy in various interest groups. The conclusions allow reflecting on considering the basic aspects of both concepts, their relationship, and recommendations to be incorporated in organizations in order to minimize the risks generated in the digital space that affect our physical life.